2021
DOI: 10.3390/nu13103632
|View full text |Cite
|
Sign up to set email alerts
|

High Fat, High Sugar Diet and DJOS Bariatric Surgery Influence Plasma Levels of Fetuin-B, Growth Differentiation Factor-15, and Pentraxin 3 in Diet-Induced Obese Sprague–Dawley Rats

Abstract: The liver plays a central role in glucose and fatty acid metabolism and acts as an endocrine organ that secretes hepatokines with diverse systemic effects. The study aimed to examine the influence of duodenojejunal omega switch (DJOS) bariatric surgery in combination with different diets on glucose administration parameters and hepatokines levels. After 8 weeks on high fat, high sugar diet (HFS) or control diets (CD), Sprague–Dawley rats underwent DJOS or SHAM (control) surgery. For the next 8 weeks after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…29 In an animal study, oral glucose tolerance test revealed that rats had low plasma PTX3 levels with abnormal glucose metabolism after being loaded with high fat and sugar. 30 In our previous study, we showed a significant positive relationship between the protein expression of PTX3 and glycosyltransferase 4, a cellular glucose transporter. 31 These animal studies suggested that PTX3 levels are sensitive to changes in glucose metabolism.…”
Section: Discussionmentioning
confidence: 86%
“…29 In an animal study, oral glucose tolerance test revealed that rats had low plasma PTX3 levels with abnormal glucose metabolism after being loaded with high fat and sugar. 30 In our previous study, we showed a significant positive relationship between the protein expression of PTX3 and glycosyltransferase 4, a cellular glucose transporter. 31 These animal studies suggested that PTX3 levels are sensitive to changes in glucose metabolism.…”
Section: Discussionmentioning
confidence: 86%
“…Oxidative stress in rats fed a high-fat diet also increases their glucose intolerance and insulin resistance [ 27 , 28 ]. Our previous studies in the same animal model reported that cafeteria diet impairs glucose metabolism and induces obesity, oxidative stress, and liver fat accumulation [ 11 , 29 ]. In the present study, we observed that the cafeteria diet induced significant disturbances in the antioxidant and lipid peroxidation markers in obese rats subjected to bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were fed with a high fat high sugar diet (HFHSD) comprising fats (45%) sugar (29.4%), protein (20%), and carbohydrates (35%) for a period of 12 weeks to induce obesity. A group of rats designated as normal control was given a standard pellet diet having composition; sugar (10.8%), proteins (24%), fat (4.9%), crude ashes (7 %), and crude fiber (4.7 %) for the same period [ 21 ]. All the animals had free access to diet and water ad libitum.…”
Section: Methodsmentioning
confidence: 99%